The White Terror - Bodó, Béla, author.
1 online resource.
Keywords: "The White Terror was a movement of right-wing militias that for two years actively tracked down, tortured, and murdered members of the Jewish community, as well as former supporters of the short-lived Council Republic in the years following World War I. It can be argued that this example of a programme of virulent antisemitism laid the foundations for Hungarian participation in the Holocaust. Given the rightward shift of Hungarian politics today, this book has a particular resonance in re-examining the social and historical context of the White Terror"--